The Notary's Function in Drafting Fiduciary Security Deeds Involving Patent Rights as Collateral - Yohana Maranatha; Nadia Inggrida Hartono (Unnes Law Journal, 2023)
Government Regulation Number 24 of 2022 on the Creative Economy outlines the implementation of the Intellectual Property-Based Financing Scheme, wherein both banks and non-banking financial institutions leverage Intellectual Property as collateral. This includes fiduciary guarantees over Intellectual Property, contracts within Creative Economy activities, and/or claims within Creative Economy activities. Notably, Patents, a subset of Intellectual Property, can serve as collateral per Article 108 paragraph (1) of Law Number 13 of 2016 concerning Patents, allowing "patent rights to be used as objects of fiduciary guarantee." The provision of funding through financial institutions, be they banks or non-banking entities, closely aligns with the collateralization aspect, involving the duties and responsibilities of Notaries. This raises inquiries into the Role of Notaries in Intellectual Property-Based Financing and the Collateralization of Patents as governed by Government Regulation Number 24 of 2022 on the Creative Economy. Employing a juridical-normative approach and incorporating interviews with relevant stakeholders involved in fiduciary guarantee deed preparation, this research aims to discern the roles and responsibilities of Notaries in drafting fiduciary guarantee deeds incorporating patents as collateral objects. Furthermore, the study seeks to establish the Mechanism for Determining the Economic Value of a Patent as agreed upon in the Fiduciary Guarantee Deed.